Propiedades químicas del Bokashi preparado con diferentes residuos vegetales y animales. - Vera Cerna, Washington Ezequiel (2019)
Bokashi is a Japanese word that means "fermented organic matter", this fertilizer is left to decompose in an aerobic process of materials of animal or vegetable origin, the improper use of chemicals affects agricultural production and also people who are in daily contact with such inputs and tend to be exposed to chronic diseases, this research aims to evaluate the chemical properties of Bokashi prepared with different plant and animal waste, which is aimed at promoting the use of organic agriculture, under the indication of contributing to agricultural improvement, socioeconomic and environmental. It was carried out in the Finca of the sector "La Cadena" of the canton Las Naves, province of Bolívar, by Ing. César Varas Maenza. Two factors were studied, being factor A: vegetable waste: rice husk and cocoa husk; factor B: animal waste types of manure: pollinaza, bovinaza and equinaza, with the combination of the factors six treatments were obtained: rice husk plus pollinaza, rice husk plus bovinaza, rice husk plus equinaza, cocoa husk plus pollinaza, cocoa husk plus bovinaza and cocoa husk plus equinaza. The treatment of rice husk plus bovine obtained 22 days to decompose. The results of the temperature measurements at the beginning and at the end of the trial, reflected statistical differences, the rice husk plus pollinaza treatment reached higher temperature at the beginning 41.53 oC, on the other hand we have that the rice husk plus bovinaza treatment obtained 32.7 oC at the end of the trial, the moisture content of the bokashi mounds recorded averages ranging from 52.48% to 56.23%, the final result showed that the treatment cocoa husk plus equinaza reached the highest pH of 8.3, the treatment cocoa husk plus equinaza obtained a lower final weight with 36.61 kg, reflecting a weight loss of 8.84 kg. Keywords: Bokashi, organic agriculture, plant residues, manure